Removal of Lithium onto chitosan derivative using Taguchi method - Peter Osei Boamah; Jacqueline Onumah; Tayari Salifu; John Hendrick Essel; Benjamin Apam (Carbohydrate Polymer Technologies and Applications)
This study aimed to remove lithium from a water-based mixture using a low molecular weight chitosan derivative (LMWCHT-LA-GLA). Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), and Nuclear Magnetic Resonance (NMR) spectroscopy were used to assess the sorbent. Lithium sorption capabilities were enhanced by LMWCHT-LA-GLA's functional groups OH, NH2, and COOH. The initial concentration, sorbent dosage and pH had the biggest effects on sorption efficiency. At the ideal initial lithium content of 1 mg/L, sorbent quantity of 0.10 g and solution pH of 6, the percentage of removal was 62.75 %. The analysis of variance (ANOVA) revealed that the initial lithium concentration contributed the largest percentage (94.10 %) to the removal efficiency. Utilizing the Freundlich, Temkin and Langmuir sorption models, the experimental data were examined. The experimental data and the Langmuir isotherm agreed fairly well with a maximum sorption capacity of 7.00 mg/g. Pseudo-first- and pseudo-second-order kinetic models were used to analyze the kinetic data obtained at the optimal initial concentration. The pseudo-second-order model provided a good fit to the experimental data. Thermodynamic studies were used to determine the kind of lithium sorption. Overall results suggested that LMWCHT-LA-GLA is a promising sorbent for the removal of lithium from aqueous solution.